Preparation method and application of organic-inorganic composite hydrogel with high strength, high inorganic ratio and suitable degradability
By copolymerizing and crosslinking ultra-small calcium phosphate nanoclusters with sodium alginate, high-strength, high inorganic ratio and suitable degradability organic-inorganic composite hydrogels were prepared, which solved the problem of poor mechanical properties of existing materials in wet environments, achieved osteocyte proliferation and mineralization, and promoted the rapid repair of large-area bone defects.
Patent Information
- Application Number
- CN202510355093.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-25
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-03-25
AI Technical Summary
The existing organic-inorganic composite materials have poor mechanical properties in wet environments and are prone to ulceration, which cannot effectively support bone regeneration and repair, resulting in long osteogenesis cycles and poor osteogenesis mechanical properties.
By using ultra-small calcium phosphate nanoclusters copolymerized and crosslinking with sodium alginate, high strength, high inorganic ratio and suitable degradability are prepared to enhance the mechanical properties and biocompatibility of the material.
The organic-inorganic composite hydrogel with mechanical stability in a wet environment is realized, which significantly improves osteocyte proliferation and mineralization, promotes the rapid repair of large-area bone defects, and the material is degradable, avoiding the problem of long-term occupying space to restrict cell migration and proliferation.
Smart Images

Figure CN119857178A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedical tissue engineering, and specifically relates to a preparation method and application of a high-strength, high-inorganic ratio and suitably degradable organic-inorganic composite hydrogel. Background Art
[0002] Jaw bone destruction caused by tumors, trauma, inflammation, etc. will affect the patient's appearance and function. Every year, about 2 million patients worldwide need bone transplantation repair. Autologous bone transplantation is considered the gold standard for clinical bone transplantation, but there are problems such as limited donor tissue and the need to open a second surgical area. Although xenogeneic bone transplantation has sufficient sources, there are potential problems such as immune rejection and virus transmission. Therefore, how to obtain bionic artificial bone repair materials to quickly and effectively promote the repair of large-area bone defects is the key to solving this problem.
[0003] Bone tissue is composed of hydroxyapatite crystals and collagen fibers arranged in parallel, and is a typical organic-inorganic composite material. Therefore, organic-inorganic composite bone repair materials have become one of the hot topics in the field of tissue engineering in recent years. The organic matrices involved include synthetic ones (polyvinyl alcohol, PCL, etc.) and natural ones (sodium alginate, collagen, etc.). Among them, sodium alginate in the natural organic matrix is a natural polysaccharide extracted from kelp or sargassum of brown algae. It has excellent biosafety and biocompatibility, and has broad application prospects in wound dressings, biological tissue engineering and other fields. It has been approved by the US Food and Drug Administration for use in the biomedical field and has advantages in tissue engineering and drug delivery applications.
[0004] Inorganic matrices include calcium phosphate, calcium carbonate, silicon minerals and iron minerals. Calcium phosphate is widely present in animal bones. Therefore, calcium phosphate-based organic-inorganic composite materials are a type of advanced functional materials currently under research. Studies have shown that the mechanical strength of such composite materials is closely related to the size of calcium phosphate nanoparticles, and small-sized calcium phosphate (1-5 nm) is conducive to improving the mechanical properties of the material. However, there are still challenges in the preparation technology of small-sized calcium phosphate in existing studies, resulting in poor mechanical properties of sodium alginate-based organic-inorganic composite materials. Especially in bone regeneration and repair treatment in the wet environment of the oral cavity, the material is prone to ulceration and cannot play an early supporting role, resulting in a long osteogenesis cycle and poor osteogenesis mechanical properties. In addition, studies have shown that biomaterials that match the mechanical properties of bones are also conducive to the proliferation and mineralization of bone cells, and play a good osteoconduction and osteoinduction role. Therefore, solving the phase separation problem between organic and inorganic matrices to improve the mechanical properties of hydrogels is the key to improving the effect of bone defect repair. During tissue regeneration, the scaffold material gradually degrades to provide space for new tissues while maintaining sufficient structural integrity to support cell growth and function. However, if the material occupies space for a long time, it will limit the migration and proliferation of cells, affect the natural healing process of tissues, and may even induce inflammatory reactions and increase the risk of infection. Therefore, it is of great significance to tissue regeneration to have good mechanical properties and a degradation rate that matches tissue formation. The patent application with publication number CN115414527A discloses an organic-inorganic integrated structure formed by ultra-small amorphous calcium phosphate nanoclusters (about 1 nm in diameter) and sodium alginate and polyvinyl alcohol, which is similar to the structure of biomineralized collagen. There are potential problems in the degradation of this double network hydrogel in vivo, which may cause adverse reactions such as high antigenicity. At the same time, traditional nanocomposite hydrogels will agglomerate as the filler content increases, resulting in poor uniformity. Summary of the invention
[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide an organic-inorganic composite hydrogel with high strength, high inorganic ratio and suitable degradability for bone defect repair, as well as a preparation method and application thereof. The mechanical properties of the material are enhanced by cross-linking the organic-inorganic copolymer of nanoparticles (inorganic polyion clusters) and sodium alginate. The prepared hydrogel material with high strength, high inorganic ratio and suitable degradability can be applied to skull repair. For the extreme model of 8 mm bone injury, a good bone repair effect can be obtained in 4 weeks.
[0006] In order to achieve the above-mentioned purpose, the specific technical solutions adopted by the present invention are as follows: The present invention provides a method for preparing a high-strength, high-inorganic ratio and suitably degradable organic-inorganic composite hydrogel, the steps of which are as follows: (1) adding triethylamine as a stabilizer, calcium salt as a calcium source, and phosphoric acid as a phosphorus source into an organic solvent to generate a calcium phosphate nanocluster solution; (2) blending the calcium phosphate nanocluster solution and the sodium alginate aqueous solution to form a uniform emulsion; (3) evaporating and drying the emulsion to obtain a composite film; (4) Immersing the composite film prepared in step (3) in water to achieve swelling equilibrium, thereby obtaining the organic-inorganic composite hydrogel with an ordered structure, high strength, high inorganic ratio and suitable degradability.
[0007] The high-strength hydrogel material prepared by the present invention exhibits good mechanical properties and simultaneously has excellent biocompatibility / degradability, and is beneficial to hard tissue repair.
[0008] Preferably, in step (1), the density of the calcium phosphate nanocluster solution is 12.5 mg / mL, and the average size of the nanoparticles in the calcium phosphate nanocluster solution is 1.7 nm.
[0009] Specifically, the preparation method of the calcium phosphate nanoclusters is as follows: 11.76 g of calcium chloride dihydrate was dissolved in 880 mL of anhydrous ethanol and stirred for 1 hour. Subsequently, an anhydrous ethanol solution containing phosphoric acid (85% by volume) and triethylamine (i.e., 4.18 mL of 85% phosphoric acid + 220 mL of triethylamine + 800 mL of anhydrous ethanol) was added dropwise, and the mixture was vigorously stirred for 12 hours. After standing at room temperature for 24 hours, a white precipitate accumulated at the bottom of the solution. The solution above the white precipitate was removed by suction to obtain the calcium phosphate nanocluster solution.
[0010] Preferably, in step (2), the blending volume ratio of the calcium phosphate nanocluster solution to the sodium alginate solution is 0.25-1:1; the mass fraction of the sodium alginate solution is 0.5 wt %, and the viscosity is 200±20 mPa.s.
[0011] The cross-linking mode of the hydrogel determines its physical and chemical properties. The small-sized calcium phosphate nanoclusters and the sodium alginate molecular chains have stronger ionic bonds, which enables the gel to form a tight network. At the same time, the sodium alginate molecules give the composite hydrogel a certain deformation ability, and the maximum stress during stretching can reach 200 kPa.
[0012] Specifically, the blending conditions are: stirring speed of 500 rpm, stirring time of 3 hours.
[0013] Specifically, in step (3), the emulsion is poured into a cell culture dish with a diameter of 10 cm and naturally evaporated and dried at 25° C. for 4-7 days, wherein the volume of the emulsion is 50-100 mL.
[0014] Preferably, in step (4), the thickness of the organic-inorganic composite hydrogel is 0.2-1.0 mm.
[0015] The present invention also provides an organic-inorganic composite hydrogel with high strength, high inorganic content and suitable degradability prepared by the preparation method, wherein the organic-inorganic composite hydrogel comprises 30-70 wt% of calcium phosphate and 30-70 wt% of sodium alginate. The organic-inorganic composite hydrogel comprises 30-60 wt% of calcium phosphate and 40-70 wt% of sodium alginate.
[0016] More preferably, the composite hydrogel comprises 54 wt % of calcium phosphate nanoclusters and 46 wt % of sodium alginate.
[0017] The hydrogel prepared by using ultra-small calcium phosphate nanoclusters in the present invention can achieve sustained and stable uniformity, and the inorganic content ratio in the hydrogel can be increased to 69.4wt% at most without the collapse of the material.
[0018] Preferably, the organic-inorganic composite hydrogel has a strain range of 33% to 66%, a maximum tensile strength range of 30 to 200 kPa, and an elastic modulus range of 34 to 154 kPa.
[0019] Preferably, the degradation characteristic of the organic-inorganic composite hydrogel is that it can degrade by at least 20% within one week. The organic-inorganic composite hydrogel prepared by the present invention has a poor degree of crosslinking between organic and inorganic, and water molecules in the aqueous solution will react with sodium alginate, thereby destroying the interaction between organic and inorganic, causing the organic-inorganic composite hydrogel to collapse, that is, degrade.
[0020] The present invention also provides an organic-inorganic composite hydrogel prepared by the preparation method, or the use of the organic-inorganic composite hydrogel as a bionic periosteum in preparing a medical material for repairing hard tissue.
[0021] Preferably, the hard tissue is skull.
[0022] More preferably, the skull bone injury diameter is 8 mm (the size of the ultimate bone defect).
[0023] In the embodiment of the present invention, the high-strength, high-inorganic-ratio and suitably degradable organic-inorganic composite hydrogel was applied to an 8 mm extreme skull defect model of rats, and the repair effect within 4 weeks was significantly better than that of autologous bone transplantation.
[0024] The present invention also provides a medical material for repairing hard tissue, wherein the medical material for repairing hard tissue comprises the organic-inorganic composite hydrogel prepared by the preparation method, or the organic-inorganic composite hydrogel.
[0025] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention uses sodium alginate as an organic structural unit and calcium phosphate oligomers as inorganic structural units. The two are cross-linked through ionic bonds. Due to the small size of calcium phosphate oligomers, the bond strength of the ionic bonds is increased, which significantly improves the mechanical strength of the material, and obtains an organic-inorganic composite single network hydrogel with mechanical stability in a wet environment. The obtained material also has good biocompatibility. In addition, the material preparation method is simple and controllable. Compared with other high-strength single network hydrogels that mostly require complex chemical synthesis, this simple method has practical significance for industrial applications.
[0026] (2) The high-strength organic-inorganic composite hydrogel prepared by the present invention is conducive to the proliferation and mineralization of bone cells, achieving a more ideal bone guidance. Experimental results have shown that it has good cell compatibility and can quickly promote the repair of rat skull defects (the repair time of 8 mm extreme bone damage is shortened to 4 weeks). Compared with the control autologous bone transplant material with the best repair effect in clinical practice, the healing effect is more significant.
[0027] (3) The double network hydrogel materials in the prior art have problems with degradation in the body and may cause adverse reactions such as high antigenicity. The high-strength organic-inorganic composite hydrogel prepared in the present invention has a single network structure and exhibits good mechanical properties. At the same time, it has excellent degradability that matches the tissue, which is beneficial to hard tissue repair. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is an appearance picture of the high-strength organic-inorganic composite hydrogel obtained in Example 2 of the present invention and an appearance picture of the control group.
[0029] Figure 2 The transmission electron microscope (TEM) image of the high-strength organic-inorganic composite hydrogel obtained in Example 2 of the present invention and the TEM image of the control group are shown.
[0030] Figure 3 This is a graph showing the percentage of inorganic calcium phosphate in the organic-inorganic composite hydrogel obtained in Examples 1 to 3 of the present invention; the data points therein respectively represent the percentage of inorganic calcium phosphate in a sample; 0.0398, 0.0004, and <0.0001 all indicate significance.
[0031] Figure 4 The tensile stress-strain result comparison diagram and elastic modulus result comparison diagram of the organic-inorganic composite hydrogel obtained in Examples 1 to 3 of the present invention are shown; the data points therein respectively represent the elastic modulus result of a sample; 0.431 indicates no significance, and 0.0004 and <0.0001 both indicate significance.
[0032] Figure 5 The degradation of the organic-inorganic composite hydrogel obtained in Examples 1 to 3 of the present invention in one week.
[0033] Figure 6 The degradation of the high-strength organic-inorganic composite hydrogel prepared in Example 2 was observed under the skin of rats for one week.
[0034] Figure 7 This is a micro-CT (Micro-CT) image of the high-strength organic-inorganic composite hydrogel prepared in Example 2 after being used to repair extreme skull defects in rats.
[0035] Figure 8 This is a graph showing the bone volume fraction results after the high-strength organic-inorganic composite hydrogel prepared in Example 2 was used to repair extreme skull defects in rats; the data points therein respectively represent the bone volume fraction results of a sample; 0.677 and 0.104 indicate no significance, and 0.0007 indicates significance.
[0036] Fig. 9 Raman spectra of the high-strength organic-inorganic composite hydrogel prepared in Example 2 and the control group. DETAILED DESCRIPTION
[0037] The present invention is further described below with reference to examples.
[0038] Example 1 1) Weigh 11.76 g of calcium chloride dihydrate, dissolve it in 880 mL of anhydrous ethanol, and stir evenly for 1 hour; After mixing 220 mL of triethylamine solution with 800 mL of anhydrous ethanol, add 4.18 mL of phosphoric acid solution (85% by volume) and mix evenly for 1 hour; Slowly add the triethylamine, anhydrous ethanol, and phosphoric acid mixed solution into the calcium chloride anhydrous ethanol solution, and continue stirring until the solution gradually changes from transparent to milky white suspension; continue stirring evenly for 12 hours; 2) The solution prepared in step 1) was allowed to stand at 25° C. for 24 hours to allow the white precipitate to completely settle to the bottom of the solution, and the upper layer was a clear solvent, and the upper layer solvent was removed by suction to obtain white ultrasmall amorphous calcium phosphate nanoclusters (the average particle size of the nanoparticles was 1.7 nm); 3) Weigh 0.5 g of sodium alginate and mix it with 100 mL of ultrapure water, stir it at 25°C for 12 hours to fully dissolve the sodium alginate, and obtain a 0.5 wt% sodium alginate solution; 4) Mix the calcium phosphate nanocluster solution (density of 12.5 mg / mL) and the sodium alginate solution in a volume ratio of 0.25:1, and stir at 25°C for 3 hours to allow the ultra-small particle size calcium phosphate and sodium alginate molecules to be fully cross-linked; pour the mixed solution into a plastic mold and dry it naturally, and then immerse it in water again to achieve swelling equilibrium, thereby obtaining a high-strength organic-inorganic composite hydrogel.
[0039] Example 2 The preliminary steps 1-3 are the same as in Example 1, wherein the calcium phosphate nanocluster solution and the sodium alginate solution are mixed at a volume ratio of 0.5:1, and stirred at 25°C for 3 hours to fully crosslink the ultra-small particle size calcium phosphate and sodium alginate molecules. The mixed solution is poured into a plastic mold and dried naturally, and then immersed in water again to reach swelling equilibrium, thereby obtaining a high-strength organic-inorganic composite hydrogel.
[0040] Example 3
[0041] The preliminary steps 1-3 are the same as in Example 1, wherein the calcium phosphate nanocluster solution and the sodium alginate solution are mixed at a volume ratio of 1:1, and stirred at 25°C for 3 hours to fully crosslink the ultra-small particle size calcium phosphate and sodium alginate molecules. The mixed solution is poured into a plastic mold and dried naturally, and then immersed in water again to reach swelling equilibrium, thereby obtaining an ultra-high strength organic-inorganic composite hydrogel.
[0042] Example 4 Performance evaluation and characterization of high-strength organic-inorganic composite hydrogel A control group was set up, which was prepared using 60-80 nm hydroxyapatite particles.
[0043] The appearance of the high-strength organic-inorganic composite hydrogel prepared in Example 2 and the appearance of the control group are shown in Figure 1 As shown, the control group collapsed in water and could not form a hydrogel structure, while the hydrogel material of the present invention showed good mechanical properties and could form a high-strength hydrogel structure. At the same time, TEM observed that the high-strength organic-inorganic composite hydrogel obtained in Example 2 had a uniform and dense network structure, and the inorganic phase formed a mineralized structure along the organic phase, while the control group could not form a network structure, and there was a clear boundary between the organic phase and the inorganic phase ( Figure 2 ).
[0044] Afterwards, the inorganic calcium phosphate content in the high-strength organic-inorganic composite hydrogel prepared in Examples 1 to 3 of the present invention was tested. The test results are as follows: Figure 3As shown, the inorganic calcium phosphate accounts for 33% in the high-strength organic-inorganic composite hydrogel prepared in Example 1; the inorganic calcium phosphate accounts for 41% in the high-strength organic-inorganic composite hydrogel prepared in Example 2; and the inorganic calcium phosphate accounts for 54% in the high-strength organic-inorganic composite hydrogel prepared in Example 2. In general, the inorganic calcium phosphate accounts for 33% to 54% in the high-strength organic-inorganic composite hydrogel prepared in the present invention.
[0045] In order to explore the interaction between the inorganic phase and the organic phase in the high-strength organic-inorganic composite hydrogel of the present invention, the chemical composition and bonding state of the high-strength organic-inorganic composite hydrogel prepared in Example 2 and the control group were analyzed by Raman spectrometer and compared. The results are as follows: Fig. 9 As shown in the Raman spectrum, the PO band of the control group is at 426.3 cm -1 , while the PO band of Example 2 is at 408.5cm -1 , indicating that there is an ionic bond interaction between calcium phosphate nanoclusters and sodium alginate molecules.
[0046] In addition, the high-strength organic-inorganic composite hydrogel of the present invention was tested for its deformation resistance to evaluate the mechanical properties of the material. The tensile stress-strain results and elastic modulus results of the high-strength organic-inorganic hydrogels obtained in Examples 1 to 3 of the present invention are compared as follows: Figure 4 As shown, it can be seen that the strain range of the high-strength organic-inorganic composite hydrogel prepared by the present invention is 33%-66%, the maximum tensile strength range is 30-200 kPa, and the elastic modulus range is 34-154 kPa.
[0047] Example 5 Degradability of organic-inorganic composite hydrogel The organic-inorganic composite hydrogel prepared in Examples 1 to 3 was immersed in PBS buffer (37°C pH=7.4), and the solution was changed every day. After the samples were collected at the preset time point, they were dried in a 40°C oven and weighed. The results are as follows: Figure 5 As shown, the organic-inorganic composite hydrogels prepared in Examples 1 to 3 can be degraded by at least 20% within 1 week.
[0048] The high-strength organic-inorganic composite hydrogel prepared in Example 2 was embedded subcutaneously in 6-week-old male rats. One week after surgery, the samples were taken and embedded for HE staining. The results were as follows: Figure 6 As shown, the number of inflammatory cells in the implanted tissue was low and the hydrogel was gradually degrading.
[0049] Example 6 Experimental study on the effect of high-strength organic-inorganic composite hydrogel in skull defect repair
[0050] Application of high-strength organic-inorganic composite hydrogel: Rats were anesthetized with 0.3% sodium pentobarbital, and 4% articaine (Bilan) injection was injected locally for anesthesia and analgesia. The skin was prepared with iodine disinfection, the skin and periosteum of the rat's skull were cut, the skull was fully exposed, and a circular bone drill with a diameter of 8 mm was used to drill a defect on the top of the rat's skull to avoid damaging the meninges. The high-strength organic-inorganic composite hydrogel prepared in Example 2 was applied to the 8 mm extreme skull defect model of rats, and the repair effect within 4 weeks was significantly better than that of autologous bone transplantation ( Figure 7 , Figure 8 ). The 3D reconstruction results of Micro-CT scans showed that compared with the blank group, the hydrogel can significantly promote the repair of skull defects, the range of bone defects is significantly reduced, new bone tissue appears in the center of the defect within 4 weeks, and the new bone density reaches a level better than that of autologous bone treatment.
[0051] The above-described embodiment is only a preferred solution of the present invention, but it is not intended to limit the present invention. A person skilled in the relevant technical field may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.
Claims
1. A method for preparing a high-strength, high-inorganic ratio and suitably degradable organic-inorganic composite hydrogel, characterized in that: Here are the steps: (1) adding triethylamine as a stabilizer, calcium salt as a calcium source, and phosphoric acid as a phosphorus source into an organic solvent to generate a calcium phosphate nanocluster solution; (2) blending the calcium phosphate nanocluster solution and the sodium alginate aqueous solution to form a uniform emulsion; (3) evaporating and drying the emulsion to obtain a composite film; (4) Immersing the composite film prepared in step (3) in water to achieve swelling equilibrium, thereby obtaining the organic-inorganic composite hydrogel with an ordered structure, high strength, high inorganic ratio and suitable degradability.
2. The method for preparing the organic-inorganic composite hydrogel according to claim 1, characterized in that: In step (1), the density of the calcium phosphate nanocluster solution is 12.5 mg / mL, and the average size of the nanoparticles in the calcium phosphate nanocluster solution is 1.7 nm; In step (2), the blending volume ratio of the calcium phosphate nanocluster solution to the sodium alginate solution is 0.25-1:1; the mass fraction of the sodium alginate solution is 0.5 wt %, and the viscosity is 200±20 mPa.s; The blending conditions are: stirring speed of 500 rpm and stirring time of 3 hours.
3. The method for preparing the organic-inorganic composite hydrogel according to claim 1, characterized in that: In step (3), the emulsion is poured into a cell culture dish with a diameter of 10 cm and dried by natural evaporation at 25°C for 4-7 days, wherein the volume of the emulsion is 50-100 mL; In step (4), the thickness of the organic-inorganic composite hydrogel is 0.2-1.0 mm.
4. The high-strength, high-inorganic ratio and suitably degradable organic-inorganic composite hydrogel prepared by the preparation method according to any one of claims 1 to 3, wherein the organic-inorganic composite hydrogel comprises 30 to 70 wt% of calcium phosphate and 30 to 70 wt% of sodium alginate.
5. The high-strength, high-inorganic-ratio and suitably degradable organic-inorganic composite hydrogel according to claim 4, characterized in that: The organic-inorganic composite hydrogel has a strain range of 33% to 66%, a maximum tensile strength range of 30 to 200 kPa, and an elastic modulus range of 34 to 154 kPa.
6. The high-strength, high-inorganic-ratio and suitably degradable organic-inorganic composite hydrogel according to claim 4, characterized in that: The degradation characteristic of the organic-inorganic composite hydrogel is that it can be degraded by at least 20% within one week.
7. Use of the organic-inorganic composite hydrogel prepared by the preparation method according to any one of claims 1 to 3, or the organic-inorganic composite hydrogel according to claim 4, as a bionic periosteum in the preparation of a medical material for repairing hard tissue.
8. The use according to claim 7, characterized in that: The hard tissue is skull.
9. The use according to claim 8, characterized in that: The skull lesion diameter was 8 mm.
10. A medical material for repairing hard tissue, characterized in that: The medical material for repairing hard tissue comprises an organic-inorganic composite hydrogel prepared by the preparation method according to any one of claims 1 to 3.
Citation Information
Patent Citations
Preparation method of antibacterial high-strength chitosan / heparin sodion compound self-assembled hydrogel membrane
CN109384943A
GTR (guided tissue regeneration) membrane and preparation method thereof
CN109395175A
Bionic bone-like composite scaffold, preparation method and application of bionic bone-like composite scaffold in rapid bone defect repair
CN115414527A
Degradable organic-inorganic composite film and preparation method and application thereof
CN119613781A
Engineered calcium alginate and uses thereof
US20230110361A1
Cited By
Oral bone repair hydrogel periosteum material and preparation method thereof
CN120037449A
Preparation method and application of organic-inorganic composite hydrogel with high mechanical adaptability and wet adhesion stability
CN121360278A
Method for preparing and application of organic-inorganic composite hydrogel with high mechanical adaptability and stable adhesion in wet state
CN121360278B